The Influence of Social Media Usage, Knowledge Sharing, and Learning Organization on Employee Performance (A Study on Fulltiime Employees at Hotel Merapi Merbabu) - Stevani, Imelda; Probosari, Ninik (Universitas Mercu Buana, 2025)
This research aims to explore and analyze the impact of social media usage, knowledge sharing, and learning organization on the performance of full-time employees at Hotel Merapi Merbabu. The study population includes full-time employees, and purposive sampling was utilized to select 92 respondents. Data collection was conducted through online questionnaires distributed via Google Forms, and the data were analyzed using SPSS software. The findings indicate that social media usage significantly and positively influences employee performance. Likewise, knowledge sharing and the learning organization both have significant positive effects on employee performance. These results highlight that establishing an effective learning organization, improving knowledge sharing, and leveraging social media effectively can be strategic methods to enhance employee performance in the hospitality sector.